Analisis Hukum Koperasi Simpan Pinjam di Nagari Abai Siat: Tinjauan Hukum Ekonomi Syariah - Hasibuan, Herianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the legal aspects of the savings and loan cooperatives in Nagari Abai Siat with the perspective of Islamic economic law. The method used in this study is qualitative, with the type of research in the form of field research. Data collection techniques are carried out through interviews and documentation. The results showed that the practice of Murabahah Bil Wakalah was carried out based on negotiation agreements, where the conditions set were met by Savings and Loan Cooperative customers in Nagari Abai Siat. This murabaha practice is seen in the commodity of goods sold to customers, and is allowed to combine murabaha and wakalah contracts by considering the benefit of individuals. The review of Islamic economic law is carried out based on the rules in Islamic law that has been recognized by the National Sharia Council (DSN) and the Sharia Supervisory Board. In its application, Islamic economic law emphasizes the relationship between customers and suppliers, thus allowing commodity purchases in accordance with the initial agreement and clear objectives.